(y-6/y)-6/y=(y+6)/(y-6)

Simple and best practice solution for (y-6/y)-6/y=(y+6)/(y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y-6/y)-6/y=(y+6)/(y-6) equation:



(y-6/y)-6/y=(y+6)/(y-6)
We move all terms to the left:
(y-6/y)-6/y-((y+6)/(y-6))=0
Domain of the equation: y)!=0
y!=0/1
y!=0
y∈R
Domain of the equation: y!=0
y∈R
Domain of the equation: (y-6))!=0
y∈R
We add all the numbers together, and all the variables
(+y-6/y)-6/y-((y+6)/(y-6))=0
We get rid of parentheses
y-6/y-6/y-((y+6)/(y-6))=0
We calculate fractions
-5y^2)+(-((y+6)*y)/(-5y^2)+y+(-6*(y-6))-6)/(=0
We calculate terms in parentheses: -((y+6)*y)/(-5y^2), so:
(y+6)*y)/(-5y^2
determiningTheFunctionDomain -5y^2+(y+6)*y)/(
We multiply all the terms by the denominator
-5y^2*(+(y+6)*y)
Back to the equation:
-(-5y^2*(+(y+6)*y))
We calculate terms in parentheses: +(-6*(y-6)), so:
-6*(y-6)
We multiply parentheses
-6y+36
Back to the equation:
+(-6y+36)
We get rid of parentheses
-5y^2)+(-(-5y^2*(+(y+6)*y))+y-6y+36-6)/(=0
We multiply all the terms by the denominator
()*(-((-5y^2*(+(y+6)*y)))*(+y*(-6y*(+36*(-6)-5y^2=0

See similar equations:

| 5-4x=8x+6 | | 3x=6 7 | | F(z)=2z-8/7z+2 | | x^2-12x+67=0 | | 0.3=0.5^x | | 3x-3+22=4x-1+9x | | 3.6=1.2r | | -3(k-1)=3(k+1)-48 | | 4x-2(2-3x)=4(x-4)-6 | | 8y-4×=12 | | 4(k-4)-3(k+1)-14=-26 | | X+x+6=20-x | | x^2+10x-24=-9 | | 3x-3+22=5x-1+8x | | 25-3x=5+x | | 12P=3b^2 | | -5(3w+1)-w=43 | | 0=28x-3x^2 | | n+7/9=17/18 | | 9k×96=98;K= | | -500x(2x-9)=0 | | 4x=9x-2 | | 1/x+1/7=3/7 | | 2x+18=19+x | | k-7/8=3/8 | | 180=x+x+2x | | 6h=7=3(4h-71)-8 | | X-2(143-x)=37 | | 6(3-2x)-12=-4(5x-4) | | 180=7x+3x+90 | | 6(3-2x)-12=4(5x-4) | | 4.9t^2+1.55t-2.2=0 |

Equations solver categories